History of mechanical staple surgical suture (review of literature) - A. L. Akopov; D. Yu. Artioukh; T. F. Molnar (Вестник хирургии имени И.И. Грекова, 2021)
Modern surgery is difficult to imagine without mechanical stapling devices. The objective of the study was to trace the continuity of the development of mechanical stapling technology by European and American surgeons. The main step that led to this technological development was the idea of using a simple paper staple for suturing of human tissue. The first time the mechanical stapling device was used on a human was 9th May, 1908 in Budapest. Subsequently, surgeons and engineers of Europe, primarily Hungary (Austria-Hungary) (H. Hultl, V. Fischer, A. von Petz, etc), Germany (H. Friedrich, etc.) and the USSR (V. Gudov, V. Demikhov, P. Androsov, etc) refined the mechanical principles and practical implications of this new technology. By the mid-1950s, two types of devices were manufactured in the USSR for simple suturing tissues such as the pulmonary parenchyma or bronchus and for the construction of anastomosis. The disadvantages of these devices could be attributed the requirement of delicate manual loading of small metal staples into the cartridge and assembling of sterile parts immediately prior to application. A group of surgeons and engineers led by an American thoracic surgeon, Mark Ravitch, managed to overcome these disadvantages by making devices user-friendly, launched their production in the USA and even organized a training network for surgeons wishing to use the new instruments. The history of mechanical stapling devices illustrates the successful realization of novel ideas that were supported by technological advances and the professional ambitions of surgeons.